Latinity and literary society at Rome - Bloomer, W. Martin (University of Pennsylvania Press, 1997)
Latinity and Literary Society at Rome reaches back to the early Roman empire to examine attitudes toward Latinity, reviewing the contested origins of scholarly Latin in the polemical arena of Roman literature. W. Martin Bloomer shows how that literature's reflections on correct and incorrect speech functioned as part of a wider understanding of social relations and national identity in Rome. Bloomer's investigation begins with questions about the sociology of Latin literature - what interests were served by the creation of high style and how literary stylization constituted a system of social decorum - and goes on to offer readings of selected texts. Through studies of works ranging from Varro's De lingua latina to the verse fables of Augustus's freedman Phaedrus to the Annals of Tacitus, Bloomer examines conflicting claims to style not simply to set true Latin against vulgarism but also to ask who is excluding whom, why, and by what means.